Development of monoclonal antibodies against bovine herpesvirus-1 (BHV-1) - Kaur, Gurpreet; Dwivedi, P N; Ramneek, Ramneek; Maiti, N K (The Indian Journal of Animal Sciences, 2012)
The BHV-1 antigen was produced in bulk by propagating BHV-1 in Madin Darby bovine kidney cell line. The antigen purified by 20–40% sucrose density gradient centrifugation was confirmed for presence of virus. The BALB/C mice were immunized by purified virus via intraperitoneal route. The spleenic lymphocytes from immunized mice were fused with myeloma cells using polyethylene glycol as a fusion agent and suspended in HAT (hypoxanthine aminopterin thymidine) medium for differentiation of hybrids. A total of 11 clones were observed, out of which 7 were positive for antibody production. The supernatant of all the positive clones showed very low concentration of antibody, except the clone B6.1, where the concentration of antibody was higher than other positive clones. The culture supernatant of B6.1 hybrid clone was isotyped by enzyme linked immunosorbent assay (ELISA) based isotyping kit and isotype of monoclonal antibody was of IgM class. In western blotting, the IgM monoclonal antibody identified the 27 KD protein of BHV-1.